Canada-Mexico exporting guide: documents and regulations for exporting to Mexico (External Affairs and International Trade Canada OttawaCA, 1993)
Provides an overview of distribution, transportation, documentation and customs regulations. Includes a section which summarizes the substantial changes to customs procedures that will come into force if the North American Free Trade Agreement (NAFTA) goes into effect as scheduled on January 1, 1994.
DC